Bystander Interventions on Behalf of Sexual Assault and Intimate Partner Violence Victims. Issue 7 (April 2020) - Weitzman, Abigail; Cowan, Sarah; Walsh, Kate
Using newly available U.S. nationally representative data from the No More study ( N = 1, 307), this article investigates (a) knowledge of sexual assault and intimate partner violence (IPV) victims within one's social network; (b) who intervenes, whom they intervene on behalf of, and how they intervene; and (c) the perceived barriers to intervening in IPV specifically. The findings reveal that knowledge of violence, the likelihood of intervening, and the intervention approaches taken all vary demographically and by violence type. Among respondents who have known a victim, one- third report having intervened for sexual assault, while one-half report having intervened for IPV. For both types of violence, respondents are more likely to have intervened on behalf of family or friends than on behalf of more distant network members. However, respondents are more likely to have solicited the help of authorities and less likely to have offered safe haven in instances of sexual assault than in instances of IPV. The most commonly cited barriers to IPV intervention include fear of injury, fear of misinterpretation, and belief that IPV is a private matter, though these vary across demographic groups. These findings indicate that the decision to intervene is highly contextual—contingent on the individual characteristics of the intervener, situational characteristics of the violence, and the relationship between the intervener and the victim.